Bone SPECT/CT of Femoral Head Subchondral Insufficiency Fracture. (September 2015) - Motomura, Goro; Yamamoto, Takuaki; Karasuyama, Kazuyuki; Iwamoto, Yukihide
<x xml:space="preserve">Abstract</x> Abstract Subchondral insufficiency fracture of the femoral head may be confused with osteonecrosis, mainly because of radiological overlap. SPECT/CT with Tc-99 m hydroxymethylene diphosphonate images in 7 patients with subchondral insufficiency fracture were retrospectively reviewed and compared with those from 11 patients with symptomatic early osteonecrosis. In all of the hips with subchondral insufficiency fracture, SPECT/CT showed increased uptake at the subchondral lesions of the femoral head. On the other hand, in all of the hips with osteonecrosis, absence of uptake was confirmed at the subchondral lesions. SPECT/CT may assist in differentiating subchondral insufficiency fracture from osteonecrosis.